2011
DOI: 10.1016/j.neuroimage.2011.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Brain dynamics of upstream perceptual processes leading to visual object recognition: A high density ERP topographic mapping study

Abstract: Recent studies suggest that visual object recognition is a proactive process through which perceptual evidence accumulates over time before a decision can be made about the object.However, the exact electrophysiological correlates and time-course of this complex process remain unclear. In addition, the potential influence of emotion on this process has not been investigated yet. We recorded high density EEG in healthy adult participants performing a novel perceptual recognition task. For each trial, an initial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 126 publications
4
37
1
Order By: Relevance
“…4A and 4B). Similarly to our previous study 397 (Schettino et al, 2011), we found a reliable topographical change across recognition levels 398 immediately following the exogenous N1 and P2 ERP components (Fig. 4B) 6 .…”
Section: Topographic Analysis Of Erps Recorded During the Unfolding Tsupporting
confidence: 87%
See 4 more Smart Citations
“…4A and 4B). Similarly to our previous study 397 (Schettino et al, 2011), we found a reliable topographical change across recognition levels 398 immediately following the exogenous N1 and P2 ERP components (Fig. 4B) 6 .…”
Section: Topographic Analysis Of Erps Recorded During the Unfolding Tsupporting
confidence: 87%
“…Moreover, we replicated our previous results (Schettino et al, 2011) and found that, regardless of 528 the memory status of the scenes (old vs. new), participants dwelt longer on emotional compared 529 to neutral scenes (Fig. 1B).…”
Section: Prolonged Exploration For Emotional Compared To Neutral Scensupporting
confidence: 85%
See 3 more Smart Citations